PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VI ASDN 011 BUKIT GAJAH KECAMATAN UKUI - Rohlina Tambunan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low science learning outcomes of students. Of the 20 students, only 7 students (42.31%) achieved mastery learning, while the average learning outcome was only 65.38. This study aimed to improve students’ science learning outcomes through the implementation of the Quantum Teaching learning model. This research employed classroom action research (CAR) conducted in two cycles. The results showed that students’ learning outcomes as well as teacher and student activities improved in each cycle. The average basic score was 65.38. In the first cycle, the average score increased to 69.08, representing an improvement of 5.66%. In the second cycle, the average score increased significantly to 85.54, with an improvement of 23.83%. Teacher activity also increased in each cycle. In the first cycle, teacher activity at the first meeting reached 66.7% (sufficient) and increased to 75% (good) at the second meeting. In the second cycle, teacher activity increased to 83.3% (good) at the first meeting and reached 95.8% (very good) at the second meeting. Similarly, student activity showed continuous improvement. In the first cycle, student activity reached 62.5% (sufficient) at the first meeting and increased to 70.8% (good) at the second meeting. In the second cycle, student activity increased to 79.2% (good) at the first meeting and reached 91.7% (very good) at the second meeting. Based on these results, it can be concluded that the application of the Quantum Teaching learning model can effectively improve science learning outcomes and student participation.